Genetic Diversity in Fruit Quality Traits in Cornelian Cherry (Cornus mas L.) - Ercisli, Sezai; Orhan, Emine; Esitken, Ahmet (Asian Journal of Chemistry, 2010)
In this study, some important fruit traits were screened in cornelian cherry (Cornus mas L.) types from the Uzundere district of Erzurum, Turkey. Twenty six types collected from Uzundere district were assessed for harvest date, fruit weight, fruit dimensions, fruit flesh ratio, fruit skin colour, total soluble solids, vitamin C, acidity and pH. The results showed tremendous variation. The types exhibited a range of 1.46–3.81 g for fruit weight, 79–88% for fruit flesh ratio, 36–74 mg/100 mL for ascorbic acid, 13–21% for total soluble solid and 1.14–2.77% for acidity. Three types had yellow fruit, while the others had fruit of various shades of red.